Maintaining protection against invasive bacteria with protein-polysaccharide conjugate vaccines. - Pollard, A; Perrett, K; Beverley, P (2009)
Polysaccharide-encapsulated organisms are the leading cause of bacterial meningitis and pneumonia in children. The use of protein-polysaccharide conjugate vaccines in developed countries over the past two decades has markedly decreased the burden of disease and mortality from these organisms through direct protection of the immunized and through herd immunity. In the next decade, the widespread use of conjugate vaccines in the developing world should prevent millions of deaths. In this Science and Society article, we describe how vaccine-induced immunity wanes rapidly after vaccination in early childhood and argue that strategies that sustain protection in the population must be considered.